Adolescent Connectedness: A Scoping Review of Available Measures and Their Psychometric Properties - Too, Ezra K.; Chongwo, Esther; Mabrouk, Adam; Abubakar, Amina (Frontiers in Psychology, 2022)
Introduction: Adolescent connectedness, a key component of positive youth development, is associated with various positive health outcomes. Several measures have been developed to assess this construct. However, no study has summarized data on the existing measures of adolescent connectedness. We conducted this scoping review to fill this gap. We specifically aimed to: (i) identify the existing measures of adolescent connectedness, (ii) determine the most frequently used measures among the identified measures, and (iii) summarize the psychometric properties of these measures with a keen interest in highlighting their cross-cultural utility and validity. Methods: We searched CINAHL, Embase, PsycInfo, PubMed, and Web of Science databases for relevant articles published since database inception to 7th February 2021. Our search structure contained the key words “Adolescents”, “Connectedness”, and “Measures”. We also searched Open Grey for potentially relevant grey literature. Results: We identified 335 measures from 960 eligible studies assessing various domains of adolescent connectedness, including school, family, community, peer, ethnic, racial, cultural, religious/spiritual, and self-connectedness. Most of the included studies (72.1%) were from North America and Europe. Most of the measures (n=132, 39.4%) were measures of school connectedness among adolescents. Of the identified measures, 60 of them met our criteria of frequently used measures (i.e the top five most used measures per domain of connectedness). These frequently used measures were used across 481 of the included studies with 400 of them reporting their psychometric properties. The reported reliability of these measures was adequate (Cronbach’s alpha ≥ 0.70) in 89.8% of these studies. These measures also appeared to be valid in terms of their face, content, construct, criterion, convergent, discriminant, concurrent, predictive, measurement invariance, and cross-cultural validity. Conclusions: There exists a wide array of measures of adolescent connectedness. Sixty of these measures have been frequently used across studies and appear to be reliable and/or valid. However, this evidence is mostly from North America and Europe. This is a reflection of the limitation of this review where only studies published in English were considered. It might also reflect the paucity of research in other regions of the world. More research is needed for clearer insights.